The relationship between job satisfaction and performance: a case study at KEMAS Jempol Negeri Sembilan - Hamisan, Janawatul Fieza (2004)
Individual satisfaction in their work place is related to the fulfillment to their basic need. The more the need are satisfied, the greater the degree of a person ‘s job satisfaction. Workers satisfactions among important element required in delivering quality services to the society, the aim of this study is to determine workers satisfaction level in relation to the performance of work also relation to their basic need and suggest way to motivate the worker. A survey using structural questionnaires was administered to the staff in KEMAS for data collection. All the data analyzed using the statistical package for social sciences (SPSS). The study reveals those satisfaction and performance workers are interrelated each other. The percentage of level satisfaction in term of their work 94% said that they are satisfied and 6% said they are not satisfied with theirs work. Meanwhile 94% are satisfied in their organization structure and 6% are not satisfied with their organization. In KEMAS it shows that it was a government agencies that successful in the fulfill the basic need of the worker. To improve quality of the work performance, the worker’s satisfaction must be enhancing through several way (Recommendation) that will be explain further. The KEMAS should act and identifying the factors contributes to employee’s satisfaction in order to ensure good work performance. It was hope that the result from the study will help government as well as KEMAS organization to increase the efficiency of management in satisfying their workers basic needs.